Undress and flee. Fugue exercises in three Central American narrators: Jacinta Escudos, María del Carmen Pérez Cuadra and Jessica Isla - Jossa, Emanuela (2022)
The article proposes the study of three stories by three Central American women writers: “Correr desnuda” by Jessica Isla, “Muñeca rota” by María del Carmen Pérez and “Yo, cocodrilo” by JacintaEscudos, which share the thematization of flight. Starting from the idea of political “disempowerment” in Central American literature, from the supposed cynicism of the narrative of the last decades, the intention of the research is to investigate the possible disruptive potential of flight in a local and global context supposedly defined by impotence and resignation. Escape is considered a negative action that, instead of directly addressing situations of oppression, acts indirectly, through disobedience, and this notion of escape is associated with the potentiality of bodies and a nonconformist becoming.